Association between dairy consumption, dietary calcium intake and general and abdominal obesity among Iranian adults. Issue 5 (September 2018) - Sadeghi, Omid; Keshteli, Ammar Hassanzadeh; Doostan, Farideh; Esmaillzadeh, Ahmad; Adibi, Peyman
Abstract: Aim: To assess the association of dairy consumption and dietary calcium intake with general and abdominal obesity in a large sample of Iranian adults. Methods: In this cross-sectional study, dairy consumption and dietary calcium intake were assessed using a validated dish-based 106-item semi-quantitative food frequency questionnaire in 6582 Iranian adults aged 18–55 years living in Isfahan. A self-administered validated questionnaire was used to collect data on anthropometric measures. Overweight or obesity was considered as body mass index ≥25 kg/m 2, and abdominal obesity as waist circumference ≥88 cm for women and ≥102 cm for men. Results: Mean age of study participants was 36.8 ± 8.1 years. Compared with the lowest quartile, men in the highest quartile of dietary calcium intake had greater odds for general obesity (OR: 1.29, 95% CI: 1.03-1.60). This relationship was significant even after adjustment for age and energy intake (OR: 1.28, 95% CI: 1.03-1.60). However, such relationship was not seen in women. No other significant associations were observed between dairy and dietary calcium intake with general or abdominal obesity. Conclusion: Dietary calcium intake was positively associated with general obesity in men, but not in women. No significant association was seen between dairy consumption and general or central adiposity.